The efficiency of using the body condition index for improving management in dairy farms - Stelian Sertu; Vlad Ber (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
The present work was carried out for the economic efficiency of dairy cow farms by using the body condition index. The body condition index is a subjective indicator that evaluates the subcutaneous fat deposits of dairy cows. For its interpretation, a scale from 1 to 5 with fragmentation from 0.5 points to 0.5 points is used. With the help of this indicator, the maintenance condition of the cows is monitored and the fodder ration is made more efficient so that there are no cachectic or obese animals in the herd. The present research was carried out at the Research and Development Institute for the Breeding Cattle of Balotesti, on a herd of 72, cows of the Romanian Black Spoted breed. This work was carried out to correct the production and reproduction deficiencies with the help of the maintenance condition of the cows. The body condition index was reported both to the reproductive indicators: the number of IA/G, service-period and the calving interval, as well as to the production indicators: milk production on the control day and milk production/lactation. From the analyzed data, it was found that by using this indicator, the economic efficiency of the farm increased by improving the production and reproduction performances.
Keywords: Q01; Q18; 330; body condition score; cow; index production and reproduction